Exploring Psychosocial Well-being and Social Connectedness in Northern Uganda - Horn, Rebecca (World Bank, Washington, DC, 2014)
This paper describes research conducted as the first stage in the process of developing a structured interview schedule to assess psychological distress, empowerment, social connectedness, economic well-being, and other variables among women in the Acholi region of Uganda. An interview schedule was developed following a review of the literature, individual interviews with women in northern Uganda, and group discussions with community members, members of women's groups, and community leaders. Following initial testing of the entire interview schedule, the reliability and validity of two sections-measures of psychological distress and social connectedness, were explored in more detail. Initial analysis suggests that both are potentially useful with this population. However, the measure of psychological distress did not distinguish clearly between a group of women identified by a local community-based organization (CBO) as showing signs of psychological distress and a group of women showing no such signs. Additional work is required to confirm the validity of the psychological distress scale used. It was found that psychological well-being was more closely associated with the amount of social support a woman receives than with how many social activities or groups she is involved with. Involvement in groups may not, in itself, alleviate psychological distress, but the practical and emotional support provided by friends, neighbors, and relatives is likely to have a positive effect. Some evidence was found that there is a relationship between involvement in religious activities and psychological well-being. Psychological distress is often accompanied by poor physical health. Although further research is required to clarify the nature of these relationships, initial findings suggest that organizations that aim to improve psychological well-being would do well to address physical health problems as a priority, and may wish to explore ways in which women experiencing psychological distress could link with religious organizations.